Comparative simulation study of gas-phase propylene polymerization in fluidized bed reactors using aspen polymers and two phase models - Ahmad, S.; M.A., H.; Sabri, M.F.; Navid, M. (Chemical Industry and Chemical Engineering Quarterly, 2012)
A comparative study describing gas-phase propylene polymerization in fluidized-bed reactors using Ziegler-Natta catalyst is presented. The reactor behavior was explained using a two-phase model (which is based on principles of fluidization) as well as simulation using the Aspen Polymers process simulator. The two-phase reactor model accounts for the emulsion and bubble phases which contain different portions of catalysts with the polymerization occurring in both phases. Both models predict production rate, molecular weight, polydispersity index (PDI) and melt flow index (MFI) of the polymer. We used both models to investigate the effect of important polymerization parameters, namely catalyst feed rate and hydrogen concentration, on the product polypropylene properties, such as production rate, molecular weight, PDI and MFI. Both the two-phase model and Aspen Polymers simulator showed good agreement in terms of production rate. However, the models differed in their predictions for weight-average molecular weight, PDI and MFI. Based on these results, we propose incorporating the missing hydrodynamic effects into Aspen Polymers to provide a more realistic understanding of the phenomena encountered in fluidized bed reactors for polyolefin production.